MR signal intensity: staying on the bright side in MR image interpretation - Annette H M van der Helm-van Mil; Monique Reijnierse; Tom W J Huizinga; Johan L Bloem (RMD Open)
Abstract In 2003, the Nobel Prize for Medicine was awarded for contribution to the invention of MRI, reflecting the incredible value of MRI for medicine. Since 2003, enormous technical advancements have been made in acquiring MR images. However, MRI has a complicated, accident-prone dark side; images are not calibrated and respective images are dependent on all kinds of subjective choices in the settings of the machine, acquisition technique parameters, reconstruction techniques, data transmission, filtering and postprocessing techniques. The bright side is that understanding MR techniques increases opportunities to unravel characteristics of tissue. In this viewpoint, we summarise the different subjective choices that can be made to generate MR images and stress the importance of communication between radiologists and rheumatologists to correctly interpret images.